Ancient metallurgical traditions and connections around the caput Adriae - Giumlia-Mair A. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2009)
In the last decade several archaeological projects concerning metallurgical tradition and techniques, were carried out on metal finds from various sites around the Northern Adriatic and in the Eastern Alps. The pieces, made of different metals, are dated to various periods, between the Late Bronze Age and Late Antiquity. The results of different kinds of analytical techniques, applied to several hundreds of archaeological metal artefacts from this area, are presented and evaluated in the paper. The different metallurgical techniques and traditions, identified during the researches are illustrated, compared and interpreted. An overview of the available data and of the general trends of ancient metallurgy in this broader area is attempted.